Surface modification of a POSS-nanocomposite material to enhance cellular integration of a synthetic bioscaffold. (March 2016) - Crowley, Claire; Klanrit, Poramate; Butler, Colin R.; Varanou, Aikaterini; Platé, Manuela; Hynds, Robert E.; Chambers, Rachel C.; Seifalian, Alexander M.; Birchall, Martin A.; Janes, Sam M.
Abstract: Polyhedral oligomeric silsesquioxane poly(carbonate-urea) urethane (POSS-PCU) is a versatile nanocomposite biomaterial with growing applications as a bioscaffold for tissue engineering. Integration of synthetic implants with host tissue can be problematic but could be improved by topographical modifications. We describe optimization of POSS-PCU by dispersion of porogens (sodium bicarbonate (NaHCO3 ), sodium chloride (NaCl) and sucrose) onto the material surface, with the principle aim of increasing surface porosity, thus providing additional opportunities for improved cellular and vascular ingrowth. We assess the effect of the porogens on the material's mechanical strength, surface chemistry, wettability and cytocompatibilty. Surface porosity was characterized by scanning electron microscopy (SEM). There was no alteration in surface chemistry and wettability and only modest changes in mechanical properties were detected. The size of porogens correlated well with the porosity of the construct produced and larger porogens improved interconnectivity of spaces within constructs. Using primary human bronchial epithelial cells (HBECs) we demonstrate moderate in vitro cytocompatibility for all surface modifications; however, larger pores resulted in cellular aggregation. These cells were able to differentiate on POSS-PCU scaffolds. Implantation of the scaffold in v ivo demonstrated that larger pore sizes favor cellular integration and vascular ingrowth. These experiments demonstrate that surface modification with large porogens can improve POSS-PCU nanocomposite scaffold integration and suggest the need to strike a balance between the non-porous surfaces required for epithelial coverage and the porous structure required for integration and vascularization of synthetic scaffolds in future construct design.